The Editor's Corner; Meet ACE Authors - R E. Stevenson (Journal of Applied Communications, 1971)
Editorial back matter for vol. 54, no. 3 (July-Sept. 1971) of ACE, the official journal of the American Association of Agricultural College Editors.